InGaAs layer effect on the growth of AlGaAs/GaAs quantum wires on V-grooved InGaAs/GaAs substrates - Lee, MS; Kim, EK; Kim, SI; Hwang, SM; Kim, CK; Min, SK; Lee, JY (PERGAMON-ELSEVIER SCIENCE LTD, 1997)
An effect of InGaAs layer on the growth of A1GaAs/GaAs quantum wires (QWRs) on V-grooved InGaAs/GaAs(100) substrates has been studied. The structures are grown by atmospheric pressure metalorganic chemical deposition (MOCVD) and characterized with scanning electron microscope, transmission electron microscope and photoluminescence (PL) measurements. The thick InGaAs layer causes to form several facets in the side walls of V-grooves. Especially, the side walls near the bottom are convexly shaped, resulting in narrowing the width near the bottom of V-groove. QWRs grown on this substrate show a blue shift in the PL spectra, while any PL signal from the top-QWLs on InGaAs layer is not obtained. These results may be originated from the narrowing effect of the InGaAs layer on the bottom and from the poor crystallinity of the top epilayer on the InGaAs layer with many dislocations. (C) 1997 Elsevier Science Ltd.
Keywords: CHEMICAL-VAPOR-DEPOSITION; GAAS; FABRICATION; LASERS; CCL4